N-monoarylacetothioureas as potent urease inhibitors: synthesis, SAR, and biological evaluation. (1st January 2020) - Li, Wei-Yi; Ni, Wei-Wei; Ye, Ya-Xi; Fang, Hai-Lian; Pan, Xing-Ming; He, Jie-Ling; Zhou, Tian-Li; Yi, Juan; Liu, Shan-Shan; Zhou, Mi; Xiao, Zhu-Ping; Zhu, Hai-Liang
Abstract: A urease inhibitor with good in vivo profile is considered as an alternative agent for treating infections caused by urease-producing bacteria such as Helicobacter pylori . Here, we report a series of N -monosubstituted thioureas, which act as effective urease inhibitors with very low cytotoxicity. One compound (b19 ) was evaluated in detail and shows promising features for further development as an agent to treat H. pylori caused diseases. Excellent values for the inhibition of b19 against both extracted urease and urease in intact cell were observed, which shows IC50 values of 0.16 ± 0.05 and 3.86 ± 0.10 µM, being 170- and 44-fold more potent than the clinically used drug AHA, respectively. Docking simulations suggested that the monosubstituted thiourea moiety penetrates urea binding site. In addition, b19 is a rapid and reversible urease inhibitor, and displays nM affinity to urease with very slow dissociation ( k off =1.60 × 10 −3  s −1 ) from the catalytic domain.